College of consults - Renken, John A. (Roman replies and CLSA advisory opinions, 2011)
"Our diocesan bishop recently died quite unexpectedly. When he became our bishop nine years ago, he established the college of consultors which comprised six priests all of whom were living when the bishop died. Six days after the bishops death, the college of consultors selected one of ist own members as the diocesan administrator. The following week, one of the members of the college of consultors died. Can he be replaced on the college before the next diocesan bishop takes possession of the diocese?"